2010
DOI: 10.1007/s11325-010-0441-5
|View full text |Cite
|
Sign up to set email alerts
|

Retropalatal Müller grade is associated with the severity of obstructive sleep apnea in non-obese Asian patients

Abstract: Physical examination may be useful for studying the upper airway in non-obese snoring patients. Flexible nasopharyngoscopy with Müller maneuver appears to be useful for evaluating the severity of OSA in non-obese patients. Retropalatal Müller grade is highly related to both the presence and severity of OSA, particularly in males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 32 publications
(42 reference statements)
2
15
1
2
Order By: Relevance
“…First, this was a retrospective study with a relatively small sample size. Second, pharyngeal changes such as enlarged tonsils, oropharyngeal crowding, elongated uvula, redundant uvula, and soft palate are also associated with OSA . However, because we did not evaluate these anatomic factors, we could not determine the effects of structural factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, this was a retrospective study with a relatively small sample size. Second, pharyngeal changes such as enlarged tonsils, oropharyngeal crowding, elongated uvula, redundant uvula, and soft palate are also associated with OSA . However, because we did not evaluate these anatomic factors, we could not determine the effects of structural factors.…”
Section: Discussionmentioning
confidence: 99%
“…This brings up the question of whether high body weight is also an important factor in non‐obese Asian patients with OSA. However, few studies have investigated the relationship between body weight and OSA in non‐obese patients …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other authors reported that retropalatal collapse was associated with OSAS due to an increased collapsibility of the lateral pharyngeal walls in this region . Wu et al reported that only retropalatal MM grade was significantly different between patients with severe OSAS in nonobese snorers . In our study, we performed only palatal surgery in patients who had obstruction in the retropalatal region according to DISE and/or MM, and we excluded patients who had retrolingual obstruction and BMI > 30 kg/m 2 .…”
Section: Discussionmentioning
confidence: 84%
“…33,34 Wu et al reported that only retropalatal MM grade was significantly different between patients with severe OSAS in nonobese snorers. 35 In our study, we performed only palatal surgery in patients who had obstruction in the retropalatal region according to DISE and/or MM, and we excluded patients who had retrolingual obstruction and BMI > 30 kg/m 2 . Although patients who underwent additional surgery due to more extensive pathology in DISE were excluded from the study, we found similar outcomes for both groups.…”
Section: Discussionmentioning
confidence: 99%